Study of socio-economic determinants in family planning - Valecha, Shalini Mahana; Ahmed, Maimoona; Sood, Akanksha (International Journal Of Community Medicine And Public Health, 2017)
Background:India is a populous country with a diverse population belonging to different religions, cultures and geographical locations. Due to these variations, factors like education, economic background, cultural and religious beliefs influence various walks of life including family planning practices. This study was done to ascertain these influences in the working lower middle class society. Methods:The research design was prospective and exploratory and carried out in a public hospital over a period of 3 months. 90 patients were studied and a prestructured proforma was used to analyse the awareness and use of family planning methods in the study group. Results:Our study showed that awareness as well as use of family planning methods are affected by various factors such as age, education level, economic status, religion & joint family system. The reasons for not using contraception were side effects, religious reasons, space constraints, limited privacy and in some cases to try for a male child. Conclusions:The government thus needs to implement strategies aimed at addressing these influences for the national family planning programs to be successful.